Tradisi Menanam Pohon Pisang - Latifa Hannum Siregar; Fatahuddin Aziz Siregar (Jurnal El-Thawalib, 2022)
The problem in this research is the tradition of planting banana trees in Horja Godang which is carried out for weddings between a man who is still a virgin and a woman who is still a girl. In this research, the formulation of the problem, namely, how does the tradition of planting banana trees occur in the horja gadang marriage in Pasar Sempurna village, Marancar sub-district. The purpose of this research is to find out how the tradition of planting banana trees in Horja Godang Marriage in Pasar Perfect Village, Subdistrict in terms of Islamic law.field study research with qualitative methods. Data collection techniques that use the data used are interviews. After the researcher obtains the data, the data is processed and analyzed to be used again for the validity of the data, as well as deductive and then reported descriptively.From the research that the researcher conducted in Pasar Perfect Village, Marancar District, the tradition of planting banana trees in Horja Godang, this marriage is very good and useful, although it is rarely done among the community because it has a very large cost.Planting banana trees at the price of goods has become a hereditary tradition that is still done today. Planting the banana tree is a series of Buddhist ceremonies carried out before the peak of the wedding partyIn Islamic law, customs also have an element of benefit and no element of harm, Or the element of benefit is greater than the element of harm. Customs in this form are fully accepted in Islamic law